Ex vivo and in vitro Monocyte Responses Do Not Reflect in vivo Immune Responses and Tolerance - Aron Jansen; Niklas Bruse; Nicole Waalders; Jelle Gerretsen; Daniëlle Rijbroek; Peter Pickkers; Matthijs Kox (Karger Publishers, 2022)
Cytokine production by ex vivo (EV)-stimulated leukocytes is commonly used to gauge immune function and frequently proposed to guide immunomodulatory therapy. However, whether EV cytokine production capacity accurately reflects the in vivo (IV) immune status is largely unknown. We investigated relationships between EV monocyte cytokine responses and IV cytokine responses in a large cohort of healthy volunteers using a highly standardized IV model of short-lived LPS-induced systemic inflammation, which captures hallmarks of both hyperinflammation and immunological tolerance. Therefore, 110 healthy volunteers were intravenously challenged with 1 ng/kg LPS twice: on day 0 to determine the extent of the IV (hyper)inflammatory response and on day 7 to determine the degree of IV endotoxin tolerance. Baseline EV monocyte cytokine production capacity was assessed prior to LPS administration. Short-term and long-term EV tolerance was assessed in monocytes isolated 4 h and 7 days after LPS administration, respectively. No robust correlations were observed between baseline EV cytokine production capacity and IV cytokine responses following LPS administration. However, highly robust inverse correlations were observed between IV cytokine responses and EV cytokine responses of monocytes isolated 4 h after IV LPS administration. No correlations between IV and EV tolerance were found. In conclusion, attenuated EV cytokine production capacity reflects ongoing IV inflammation rather than immune suppression. Results of EV assays should be interpreted with caution at the risk of improper use of immunostimulatory drugs.